Design and Development of Web-based Commerce for SMEs in East Jakarta - Dedi Purwana E. S.; Terrylina Arvinta Monoarfa; Ika Febrilia (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
This activity is a “Design and Development of a Web-Commerce-based Strategy for Promotion of Micro, Small and Medium Enterprises for SMEs in the East Jakarta Region.” This is motivated by various obstacles experienced by SMEs when they are not sufficiently competitive with competitors in the market. The disruptive era has driven changes in various aspects of life, including market behavior. It is undeniable that business digitization plays a very important role in business activities. For this reason, this program aims to make SMEs especially those in the East Jakarta area able to be competitive through the designed Web-Commerce, which is named lapaksenggol.com. The lapaksenggol.com web-commerce is a promotional media that can be used optimally by SMEs in the East Jakarta area to make it easier to expand market share and get closer to consumers. In addition, in the long term, the existence of lapaksenggol.com Web-Commerce will increase consumer awareness of the existence of SMEs, build networking with other business units, and increase market confidence in SMEs. As a result of the collaboration with the East Jakarta Regional Cooperative, SMEs and Trade Sub-Department, the soft launching of the lapaksenggol.com web-commerce was carried out on June 22, 2021, and the socialization of lapaksenggol.com to SMEs in East Jakarta on August 19, 2021.